Who Manages the Firm Matters: The Incremental Effect of Individual Managers on Accounting Quality - Wells, Kara (The Accounting Review, 2020)
ABSTRACT I investigate whether individual managers have an incremental effect on firms' accounting quality (AQ) after controlling for known determinants of AQ, time fixed effects, and firm fixed effects. To identify the manager-specific effect on firm AQ, I construct a dataset that tracks the movement of 907 managers across firms over the period 1992–2014. Results indicate that individual manager fixed effects explain a statistically and economically significant proportion of the cross-sectional variation in AQ, which is comparable to that of firm fixed effects. Variation in managerial attributes that impact AQ is applied consistently as firms switch manager-type. Using a setting of exogenous CEO turnover, I find managerial idiosyncrasies impact AQ and are not merely a reflection of firms actively choosing managers with a desired combination of managerial attributes that, in turn, impact the variability of accruals. Overall, my study underscores the importance of individual managers in the determination of AQ. Data Availability: Data used in this study are publicly available from sources identified in the text.